Table of contents and introductory materials for Vol. 23, no. 3, 2017 - Bruce Quantic (The Advocate, 2016)
Table of contents and introductory materials for Vol. 23, issue 3 (Fall - Winter 2017), including a dedication to Dr. Donald E. Hufford (1929-2016), ATE-K member and reviewer/author.